Aerobic and Resistance Exercise in Late-Onset Pompe Disease Treated with Enzymatic Replacement Therapy: a Systematic Review - Jiménez Morgan, Sergio (2016)
Purpose: to systematically review the current evidence on the effects of aerobic and resistance exercise in lateonset Pompe disease patients treated with enzymatic replacement therapy. Methods: a systematic search of the literature was conducted on Academic Search Complete, Medline with full text, SPORTDiscus, Pubmed, and Science Direct electronic databases. In addition, cross-referencing and manual search of printed journals was performed. The eligibility criteria were (a) experimental or quasiexperimental research design; (b) intervention with aerobic exercise, resistance exercise, or both; (c) published studies until August 2016; (d) studies published in English, Spanish, French or Portuguese; (e) studies on human beings. This systematic review was reported in accordance with the PRISMA statement. Results: of the 166 citations identified, 4 met the eligibility criteria and were included in the review. All studies had a small sample size, and ranged from 5 to 23 participants. In three of the studies, the training programs allowed subjects to improve physical parameters like muscular strength, endurance, core stability, and to decrease pain and fatigue. Overall, body composition remained unchanged. Conclusions: the results found in this review suggest that aerobic and resistance training may be beneficial in this population. There is a need for additional, larger sample sizes, longer studies with more homogeneous training programs on this topic. Keywords: aerobic exercise, glycogen storage disease type II, Pompe disease, resistance training, systematic review.